Beats produced between a rhythmic applied force and the resting tremor of Parkinsonism. - Walsh, E G (1979)
Rhythmic forces have been applied to the wrist of patients with Parkinsonism tremor by means of a printed motor. The tremor rate was not altered to that of the applied force. On the contrary, beats were established, the rate of which depended on the difference in rate between the tremor and the applied rhythm. Most of the observations have been for horizontal motion of the hand but similar phenomena have been seen for vertical movements, and for other parts of the body--for example, foot, elbow, finger joint, and head. The observations are regarded as supporting the view that the tremorgenic mechanism is central. There was no electromyographic evidence of servo driving or servo assistance in the genesis of the tremor.